1988
DOI: 10.1126/science.3201242
|View full text |Cite
|
Sign up to set email alerts
|

A Specific, Highly Active Malate Dehydrogenase by Redesign of a Lactate Dehydrogenase Framework

Abstract: Three variations to the structure of the nicotinamide adenine dinucleotide (NAD)-dependent L-lactate dehydrogenase from Bacillus stearothermophilus were made to try to change the substrate specificity from lactate to malate: Asp197----Asn, Thr246----Gly, and Gln102----Arg). Each modification shifts the specificity from lactate to malate, although only the last (Gln102----Arg) provides an effective and highly specific catalyst for the new substrate. This synthetic enzyme has a ratio of catalytic rate (kcat) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
175
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(192 citation statements)
references
References 25 publications
6
175
1
2
Order By: Relevance
“…An R102Q mutant enzyme of E. coli MDH had the effect of relaxing the high degree of specificity for the substrate oxaloacetate (Nicholls et al, 1992). These results were different from those for a Q102R mutant of B. stearothermophilus LDH where MDH specificity was conferred on the LDH enzyme framework (Wilks et al, 1988) and for an R102Q mutant of H . marismortui MDH where LDH activity was conferred on the MDH enzyme framework (Cendrin et al, 1993) (Fig.…”
Section: Modulation Of Substrate Specificitycontrasting
confidence: 88%
“…An R102Q mutant enzyme of E. coli MDH had the effect of relaxing the high degree of specificity for the substrate oxaloacetate (Nicholls et al, 1992). These results were different from those for a Q102R mutant of B. stearothermophilus LDH where MDH specificity was conferred on the LDH enzyme framework (Wilks et al, 1988) and for an R102Q mutant of H . marismortui MDH where LDH activity was conferred on the MDH enzyme framework (Cendrin et al, 1993) (Fig.…”
Section: Modulation Of Substrate Specificitycontrasting
confidence: 88%
“…5a). Prior reports demonstrated that the corresponding residue in bacterial LDH plays an important role in determining substrate specificity 39,40 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mutation of the corresponding residue in bacterial LDH from glutamine to arginine (Q102R) enhanced the ability of the enzyme to reduce oxaloacetate 39,40 . Therefore, we generated vectors expressing either wildtype LDHA (LDHA WT) or LDHA with a point mutation resulting in replacement of glutamine 100 with arginine (LDHA Q100R).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of malate dehydrogenase, a single point mutation was sufficient to convert it into a lactate dehydrogenase, with a k cat /K m shift of 10 7 (40). However, for many systems, larger numbers of mutations or more drastic changes are required to alter specificity (41,42).…”
Section: Table 2 Kinetic Parameters Measured For Sortase Mutantsmentioning
confidence: 99%